STUDI PERBANDINGAN PARADIGMA FUNGSIONALISMESTRUKTURALVS STRUKTURALISME LEVI-STRAUSS - Intan Sari Devi (ASKETIK: JURNAL AGAMA DAN PERUBAHAN SOSIAL, 2018)
This study aims to compare two paradigms functional paradigm (structural) vs. structuralism Levi-Strauss. To answer questions about both these paradigms will use a comparative study between functionalism paradigm theory or functionalism (structural) and developed structuralism Levi-Strauss as well as how both of these paradigms look at a structure in understanding the symptoms of socio-cultural community. The discussion of this study describes each paradigm by the basic assumptions, models, and concepts and how each of these paradigms analyzes the social phenomena of culture in society using analysis of different functionalism- (structural ) considers language as all that exists in the community has a social function and integrate structurally, but developed structuralism Levi-Strauss understand the socio-cultural phenomenon kinship system, mythology and socio-cultural issues that exist in society as a structure of the language.